2017
DOI: 10.1111/dme.13385
|View full text |Cite
|
Sign up to set email alerts
|

Glucose‐6‐phosphate dehydrogenase deficiency induced haemolysis in a woman with newly diagnosed diabetes after normalisation of hyperglycaemia

Abstract: We conclude that in order to reduce the risk of hemolysis, in an area with high incidence of G6PD deficiency, screening of the enzyme activity should be considered in newly diagnosed people with diabetes. In case of G6PD deficiency, it is advisable to correct plasma glucose level gradually in order to avoid the rapid decline in glucose availability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
(60 reference statements)
0
3
0
Order By: Relevance
“…When treated with DKA, during insulin infusion, rapid correction of prolonged hyperglycaemia may increased the inability of the red blood cells to produce NADPH. This leads to an imbalance in the consumption and production of NADPH [ 25 ]. In addition, hyperglycaemia increased the production of reactive oxygen species (ROS) in the form of superoxide [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When treated with DKA, during insulin infusion, rapid correction of prolonged hyperglycaemia may increased the inability of the red blood cells to produce NADPH. This leads to an imbalance in the consumption and production of NADPH [ 25 ]. In addition, hyperglycaemia increased the production of reactive oxygen species (ROS) in the form of superoxide [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, hyperglycaemia increased the production of reactive oxygen species (ROS) in the form of superoxide [ 26 ]. These reactive oxygen species can destroy and deform the erythrocyte membrane, which leads to erythrocytes to be fragile and prone to lysis [ 25 ]. So, it is important to avoid the rapid decline in glucose availability.…”
Section: Discussionmentioning
confidence: 99%
“…Gradual plasma glucose correction to avoid rapid decrease in glucose availability for red blood cells is likely to reduce the occurrence of hemolysis in G6PD-deficient patients [13]. Also, screening of G6PD enzyme activity should be considered in patients newly diagnosed with diabetes, especially in boys, considering the ethnic origin of the patient, to reduce the risk of hemolysis.…”
Section: Discussionmentioning
confidence: 99%
“…In G6PD deficiency, the severity of hemolysis is variable, and this hemolysis resolves when the normal metabolic balance is restored ( 3 ). It has been reported that severe hemolytic anemia due to G6PD deficiency may develop in newly diagnosed diabetes, especially during the correction of hyperglycemia, but this is very rare ( 4 , 5 ).…”
Section: Introductionmentioning
confidence: 99%